Pengaruh Penggunaan Teknologi Informasi, Efektivitas Sistem Informasi Akuntansi dan Sistem Pengendalian Internal Terhadap Kinerja Karyawan - Dwi Renaldy Putra; Cris Kuntadi; Rachmat Pramukty (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomena of the relationship or influence between variables. This article reviews the factors that influence employee performance, namely the use of information technology, effectiveness of accounting information systems and internal control systems, a literature study on human resource management. The purpose of writing this article is to build a hypothesis on the influence between variables to be used in further research. The results of this literature review article are: 1) Use of Information Technology affects Employee Performance; 2) Effectiveness of Accounting Information Systems affects Employee Performance; and 3) Internal Control System affects Employee Performance.